Educação sexual: desafios, possibilidades e percepções de estudantes sobre a homofobia - Valcarenghi, Josimar Vargas (2024)
Brazil is one of the countries with the highest rate of violence against the LGBTQIAP+ population and homophobia, which is the prejudice against this population, presents itself in different forms in society, from a more subtle form to physical violence. Educational environments play a fundamental role in breaking down this deep-rooted violence. In this context, this research aimed to analyze the effects of homophobia in the Brazilian educational context, verifying the effects of homophobia in education, building a retrospective of policies on sex education, carrying out extension activities on the subject at different levels of education and identifying homophobic responses from undergraduate students. This is a descriptive study with a qualitative-quantitative analysis, divided into two stages: 1) Activities on gender and sexuality at different levels of education and 2) an investigation into homophobia with undergraduate students. The first stage was adapted according to the age group to address issues such as gender identity, sexual orientation and social construction at different levels of education. The second part is a pilot study to identify homophobic responses from undergraduate students. The results show that it is necessary for issues relating to gender and sexuality to be dealt with in a less stigmatized and interdisciplinary way, with policies that give more support to educators, who are key players in the whole process of building an education that respects diversity. Thus, work like this is needed, with intersectoral, interdisciplinary and transdisciplinary approaches in order to reduce homophobic violence inside and outside school environments.